2012
DOI: 10.1180/claymin.2012.047.3.01
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide catalysts: Fenton and Fentonlike reactions – a review

Abstract: Iron is the fourth most common element by mass in the Earth's crust and forms compounds in several oxidation states. Iron (hydr)oxides, some of which form inherently and exclusively in the nanometre-size range, are ubiquitous in nature and readily synthesized. These facts add up to render many Fe (hydr)oxides suitable as catalysts, and it is hardly surprising that numerous studies on the applications of Fe (hydr)oxides in catalysis have been published. Moreover, the abundant availability of a natural Fe source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(218 citation statements)
references
References 104 publications
(86 reference statements)
10
200
0
8
Order By: Relevance
“…Maghemite presents the same structure as magnetite, it is also spinel ferrite and ferromagnetic. However, due to absence of Fe(II), its catalytic activity is expected to be lower than that of magnetite [45]. -FeOOH and its poorly natural counterpart, feroxyhyte ('-FeOOH), have structures based on the CdI 2 and disordered CdI 2 models, respectively [45].…”
Section: Magnetic Natural Mineralsmentioning
confidence: 99%
“…Maghemite presents the same structure as magnetite, it is also spinel ferrite and ferromagnetic. However, due to absence of Fe(II), its catalytic activity is expected to be lower than that of magnetite [45]. -FeOOH and its poorly natural counterpart, feroxyhyte ('-FeOOH), have structures based on the CdI 2 and disordered CdI 2 models, respectively [45].…”
Section: Magnetic Natural Mineralsmentioning
confidence: 99%
“…4 Fenton's reaction proceeds optimally around pH 3, thus wastewater streams need to be acidified. 5 Subsequent neutralisation leads to Fe(OH)3 precipitates as a sludge, requiring an additional separation step. 6 This complexity of the homogeneous Fenton route motivated investigations of heterogeneous Fenton-like systems, seeking to localise the Fenton process at the surface of a solid phase containing the required metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of simple Fenton-like solid catalysts are Fe (oxy)hydroxides e.g., magnetite, ferrihydrite and hematite. 5,6,8 Also attractive is magnetite (Fe3O4), which can be easily separated from the solution through its magnetism. The impact on catalytic activity of replacing Fe 2+ ion in the inverse spinel structure of Fe3O4 by other ions such as Cu 2+ , Co 2+ , Mn 2+ and Ni 2+ has also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) is an efficient Fenton catalyst among the iron oxide minerals [2,17], possibly because it accommodates both Fe(II) and Fe(III) in the structure and can be reversibly oxidized and reduced while the same structure is remained. Moreover, magnetite is a magnetic mineral and can be easily recycled in the practical wastewater decontamination.…”
Section: Fe(ii)mentioning
confidence: 99%
“…Increasing attention has been paid to heterogeneous Fentonlike reaction, due to its potential effectiveness in the mineralization of organic pollutants in a wide range of reaction pH, and limited iron leaching for catalyst recycle [1][2][3]. Recent studies showed that aqueous hydrogen peroxide can be decomposed over various solid catalysts, e.g., zeolite-supported iron [4,5], iron pillared interlayered clays [6,7], and iron oxide minerals (goethite, hematite, magnetite, and ferrihydrite), [8,9] via the Haber-Weiss mechanism (Eq.…”
Section: Introductionmentioning
confidence: 99%